Beyond mentoring : a guide for librarians and information professionals - Lowe-Wincentsen, Dawn (Chandos information professional series., 2017)
"Beyond Mentoring: A Guide for Librarians and Information Professionals looks at mentorship, mentorship programs, what works, what doesn't, and different techniques, such as group and peer mentoring. The book considers many aspects of mentoring, various programs, and their successes and failures, going beyond the usual types of mentoring by looking at newer models. An example of the cohort model from the American Library Association Emerging Leader model is included as a case study. In addition, another case study on the Sunshine State leadership Institute provides a toolkit for building your own program. The final section of the book offers perspectives and tools that people can use in designing their own programs. Provides case studies and perspectives from librarians who have been involved in mentoring programs ; Describes program types that go beyond traditional mentoring, including peer-to-peer and cohort or group mentoring ; Gives practical advice to help readers apply best practices to their own situations ; Offers a hands-on perspective of the program design process"--Provided by publisher